Structural analysis of masonry vaulted staircases through rigid block limit analysis. (February 2020) - Rossi, M.; Calderini, C.; Di Napoli, B.; Cascini, L.; Portioli, F.
Abstract: This paper investigates the structural behaviour of masonry vaulted staircases and the efficacy of different modelling strategies for the assessment of their structural safety. In particular, the present study focuses on the structural analysis of the masonry vaulted stairs of the medieval Santa Maria delle Vigne bell tower in Genoa (Italy), dating back from XVI to XVII Century. Both a limit analysis tool and a static incremental analysis using a finite element model are adopted. The limit analysis problem is formulated for a rigid block model using an iterative solution procedure to take into account crushing failure. Results indicate that crushing failure is crucial in capturing the response of this structural typology.